Cassava endophytic microorganisms of commercial plantings and ethnovarieties in three Brazilian states - Teixeira, Manoel Araújo; Melo, Itamar Soares de; Vieira, Rosana Faria; Costa, Francisco Eduardo Carvalho; Harakava, Ricardo (Pesquisa Agropecuaria Brasileira, 2007)
The aim of this work was to perform a survey of the diversity of endophytic microorganisms in cassava (Manihot esculenta Crantz) collected from commercial plantings, in the State of São Paulo, and in ethnovarieties collected in the States of Amazonas and Bahia, and also, to evaluate its potential of biological nitrogen fixation, and to produce indolacetic acid. In those States, 47 species of 27 genera were identified. Bacillus spp. was the most frequently found in all sampled regions. In Amazonas State, it was found the higher diversity of endophytic microorganisms. PCR amplifications of the nifH gene were evaluated in species of γ-Proteobacteria subgroup. IAA production was found in microorganisms isolated in cassava grown in all sampled States and belonged to the following subgroups: γ-Proteobacteria, β-Proteobacteria, Bacilli and Actinobacteria. In cassava, the occurrence of endophytic bacteria, with N-fixing and in vitro IAA-producing abilities, indicates potential for plant growth promotion.